Acceptance of Alternative Medicine in Bangladesh: A Study on Homeopathy (Bioresearch Communications, 2024)
Homeopathy is widely recognized globally, including in Bangladesh, as part of Complementary and Alternative Medicine (CAM) acknowledged by the World Health Organization (WHO). It is noted for effectively treating various conditions without adverse effects, which has garnered significant interest. This recent study investigated the acceptance of homeopathic medicine among Bangladeshi people, surveying 157 respondents. The participants comprised of 64.3% males and 35.7% females; among them a large majority (88.5%) had at least a graduate-level education, and 72.6% belonged to middle-class families. Interestingly, middle-aged individuals (45.2%) showed a particular affinity for homeopathy. This study revealed a high awareness levels among the respondents, with 89.8% familiar with homeopathic medicine and 86.6% erudite about its utilization. In addition, safety was mentioned by 65.6% of respondents, affordability by 55.4%, and effectiveness in many cases by 44.9%. However, all the above points collectively influenced their preference for homeopathy. There was a consensus among 69.4% of respondents advocating for integrating homeopathy into mainstream healthcare. The study participants endorsed few ideas including ensuring quality control of homeopathic medicines, promoting research initiatives, and providing greater integration opportunities for homeopathic practitioners within the healthcare system.Bioresearch Commu. 10(2): 1619-1626, 2024 (July)